Managing change expert solutions to everyday challenges. (Pocket mentor series., 2009)
In order to remain competitive in increasingly aggressive markets managers must adopt a positive attitude towards change. Successful managers know how to embrace change with an open mind and use it as a stimulus for new ideas, enthusiasm and progress.